Answer: x = a*y + 3
Step-by-step explanation:
To make x the subject of the equation, first, we open the bracket
4x - 12/a = y
Then cross multiply:
4x - 12 = a * y ( a*y means the product of the two variables)
Add 12 to both sides of the equation
4x = a*y + 12
Divide both sides by 4 to get the value of x
x = a * y + 12/4
x = a*y + 3
I hope this helps.
Answer:
3
Step-by-step explanation:
Given:
4 Divide by 2 and add 1
Computation;
[4 / 2] + 1
Using BODMAS rule
⇒ [4 / 2] + 1
⇒ 2 + 1
3
Answer:
-15e+14f-30
Step-by-step explanation:
First using distributive property to expand the first term:
-21e+14f-28+6e-2
Combining like terms:
-15e+14f-30
Hello I hope this helps. I'm pretty sure this is the answer.
Part A: C
Part B: A
Answer: 11.59 months
Step-by-step explanation:
You need to divide 339.12 by 29.26. Then you should check your answer by multiplying 11.59 by 29.26. Which should get you 339.1234. When you sound that you get 339.12. Hope this helps!!